Penyusunan Alat Evaluasi It Wondeshare Quiz Untuk Guru Smk N 6 Kota Bengkulu - Hermawasnsa; Yul, Fadlul Amdhi; Susanto, Edy; Alani, Gina Tri (Jurnal Kewirausahaan dan Bisnis, 2021)
The implementation of this service activity aims to improve the skills of SMK N 6 Bengkulu City teachers in compiling online evaluation tests through the Wondershare Quiz Creator application. The participants involved were 30 teachers at SMK N 6 Bengkulu City. Most teachers have problems in designing and applying technology in online evaluation. The methods used in this activity are counseling, training, and mentoring. The results obtained are an increase in teacher knowledge and skills in compiling online-based tests and the growing enthusiasm of teachers to compose tests independently by utilizing technology. This can be seen from the results of the questionnaire filled out by the participants which showed that 90% of the participants responded that the training provided benefits to the participants regarding making online-based tests through the Wondershare Quiz Creator application and other data showing 87.78% of the participants' impression that the training was interesting so that the participants felt motivated. and have skills related to making online-based tests as one of the innovations in learning evaluation